'Diplomatic Courage': A Turkish Ambassador in Sinj. Issue 2 (4th March 2023) - Kuru, Deniz
ABSTRACT: This study deals with the surprising participation of the Turkish ambassador in Croatia at the country's well-known annual Sinj Alka, an equestrian competition with a long tradition that relates to a famous victory over the Ottoman Turks in the 18th century. While the bilateral relations between Croatia and Turkey have developed since 1992 on a rather stable and positive level, the historical background has yet been marked by the legacy of the Ottoman occupation over large territories making up today's Croatia. The 2012 attendance of a Turkish ambassador at the annual festivities in Sinj, themselves also marked by Croatian nationalist frames, was the first time that a Turkish representative was among the official guests. This study employs the concept of diplomatic courage and offers a history of the present in order to show how the lenses of new diplomatic history provide a useful means to approach this historical attendance, relying most importantly on the notion of diplomatic practices. It does this via an analysis of news reports and commentaries from Croatia and Turkey while underlining the historical dimension of the bilateral relationship. The conclusion pinpoints the limits of such practices in other contexts, depending on states' foreign political choices.